Child Custody (Hadhanah) in Islamic Family Law in Minangkabau Society - Pertiwi, Dian; Firdaus, Firdaus (Jurnal El-Thawalib, 2026)
Childcare in Islamic family law in Minangkabau is interesting to study because it lies at the intersection of sharia and matrilineal customs, thereby strengthening the role of the maternal line. This dynamic becomes increasingly complex, especially in the context of divorce, so it is important to analyze how harmonization between Islamic law and customs is implemented in practice. This study aims to determine the concept of childcare (hadanah) in Minangkabau society, whether it is a manifestation of maternal nature alone or is more influenced by the social environment and local customs. This study is a field research study with a qualitative approach, which aims to describe and analyze the empirical reality of post-divorce childcare within a matrilineal kinship system. Primary data were obtained from 25 divorced married couples: mothers, a grandmother, a traditional head (penghulu or KAN), seven datuak (customary leaders), religious figures (ulama or cadiak pandai), community leaders who are considered experts and familiar with the problems in this study, and secondary data from books, articles, and documents deemed necessary. Data was obtained from observation, interviews and documentation and then analyzed using descriptive analytical techniques. These findings demonstrate maternal dominance in parenting, where mothers are not only responsible for the education and care of children but also serve as the primary breadwinners. This situation potentially puts children at risk of losing their right to attention and support from their fathers. Matrilineal kinship in Minangkabau also contributes to low paternal involvement, including the fact that children live with their mothers, the shame of visiting their ex-wife's home, and inherent traditional perceptions. Thus, the practice of hadanah in Minangkabau is more strongly influenced by local customs and traditions.